Analisis Komunikasi Penggunaan Media Sosial Instagram Terhadap Penyakit Ain Berdasarkan Perspektif Islam - Astri Dwi Andriani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The ability of Instagram users to post pictures or videos of their daily lives on social media platforms can lead to various reactions and interpretations from the generalpublic, one of which causes 'ain' disease or diseases that come from views accompanied by excessive jealousy and amazement. The purpose of this study was to analyze the relationship between social media Instagram and 'ain' disease based on an Islamic perspective. Quantitative technique with descriptive approach is used in this research. Data were collected using a questionnaire as part of the survey. Data analysis was carried out by comparing survey findings with the literature. The results showed that most of the respondents felt happy and enthusiastic when their Instagram followers responded to the photos and videos they shared. In addition, respondents know about 'ain even though they have never experienced symptoms of 'ain disease. The conclusion of the study shows that the use of Instagram social media opens the opportunity to be exposed to the disease 'ain due to a sense of pride, arrogance, envy, and a sense of amazement without being accompanied by words of blessing.